TEACHER’S SCAFFOLDING MOVES IN COMMUNICATION STRATEGIES IN SECONDARY SCHOOL EFL CLASSES - Wahyu Usadiati (Fakultas Sastra Universitas Negeri Malang, 2010)
Teachers have their own strategies in communicating their messages in EFL classes. The strategies may be in the form of verbal and nonverbal signals to get the message through to the students. The results of the study show that scaffold- ing moves were mostly used by the teacher, consisting of organizing and maintain- ing student’s interest and motivation, modeling, code switching, explaining or elabo- rating, eliciting student’s response, checking student’s comprehension, and provid- ing wait time. Non-verbal signals always occur for the accompaniment of the verba- lization of the teacher’s messages